A STIGMASTEROLGLYCpSIDE FROMTHE ROOTWOOD 9F Me/ochia umbel/a fa (Houtt) Stapf var. degrabrata K. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A stigmasterol glycoside (stigmast-5,22-dien-3-0-I3-D-glucopyranoside)has been isolated from the chloroform fraction of root wood of Me/ochia umbel/ata (Houtt) Stapf var. degrabrata K. The compound structure was determined on spectroscopic evidences including IR, 1D and 2D NMR and compared to previous data. The isolate was also active against Aspergillus niger.